In translation : reflections, refractions, transformations / Kar, P. C. (Prafulla C.); St-Pierre, Paul; Kar, P. C. - Kar, P. C.
With contributions by researchers from India, Europe, North America and the Caribbean, In Translation - Reflections, refractions, transformations touches on questions of method and on topics - including copyright, cultural hybridity, globalization, identity construction, and minority languages - which are important for the disciplinary development of translation studies but also of interest to other fields as well, most notably comparative literature, cultural studies and world literature. The volume provides a forum for new voices to be heard alongside those of well-established scholars and f.